Desenvolvimento de procedimento de extração sequencial para separação de espécies de Ni e V em petróleo - Cavalcante, Cleusa [UNIFESP] (2017)
The determination of Ni and V in crude oil has been evaluated in several scientific studies, because these elements can contribute to equipment corrosion process, contamination of catalytic processes, and the constant risk of environmental pollution. Many studies focus on the evaluation of the total concentration of these elements. However, although the total elemental concentration is important to know the chemical composition of a sample, it does not show the amount of potentially toxic compounds to the human health that may be associated with different macromolecules. Considering these notes, the aim of this paper is to present the development of a sequential extraction procedure for separation of Ni and V species. For this, samples of petroleum and certified reference material (NIST - SRM 1634C), was performed an acid digestion and analysis by GF AAS. The experimental results showed that the total concentration of elements in the crude oil were between 7.4 to 14.3 µg g-1 for Ni and 8,98 to 14.6 µg g-1 for V. The analysis of SRM 1634C showed a relative error of 5% for Ni analysis and 13% for V. The separation of species was performed by column chromatography with silica gel (as stationary phase) and employing hexane (fraction 1), toluene (fraction 2), dichloromethane + methanol (fraction 3) and methanol (fraction 4) as eluents. The extracts obtained in each fraction were analysed by GF TAAS, GC–MS and IR. The GC-MS analysis showed the following elution order: saturated compounds and aromatics (fraction 1), aromatic and cyclic compounds (fraction 2), aromatics compounds (fraction 3) and polar compounds (fraction 4). The results obtained by GF AAS showed that 100% of Ni and V contained in crude oil can be separated in 3 different extracts. Although, the IR spectrum and CG–MS analysis allow to conclude that Ni and V can be associated only to non-volatile compounds, which contain C=O, N-H and S=O bonds.